2003
DOI: 10.1016/s0741-5214(03)00912-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized study of external jugular vein patch versus polytetrafluoroethylene patch during carotid endarterectomy: perioperative and long-term results

Abstract: We can conclude, with the power limitation of the study, that carotid endarterectomy can be safely performed with either the EJV or PTFE patch. Advantages of the EJV for carotid angioplasty include no cost for material, low risk for graft infection, and preservation of the saphenous vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Grego et al prospectively compared jugular vein to PTFE patching and found no difference in stroke-free survival up to 60 months and no difference in recurrent stenosis. 17 Goldman et al compared saphenous vein, jugular vein, and Dacron patching in 275 CEAs and reported no differences in either perioperative morbidity and mortality or restenosis between any of the groups. 18 A small trial reported by Jacobowitz et al comparing jugular vein, saphenous vein, and Dacron patching, revealed a higher death rate for jugular vein compared with either saphenous vein or Dacron, and a nonsignificant higher stroke rate using jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…Grego et al prospectively compared jugular vein to PTFE patching and found no difference in stroke-free survival up to 60 months and no difference in recurrent stenosis. 17 Goldman et al compared saphenous vein, jugular vein, and Dacron patching in 275 CEAs and reported no differences in either perioperative morbidity and mortality or restenosis between any of the groups. 18 A small trial reported by Jacobowitz et al comparing jugular vein, saphenous vein, and Dacron patching, revealed a higher death rate for jugular vein compared with either saphenous vein or Dacron, and a nonsignificant higher stroke rate using jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…Although patch repair seems to be associated with less early thrombosis and late restenosis (156,157), there is a 1% risk of patch "blow-out" or infection. The choice between prosthetic patch or vein patch appears to be less critical (158,159).…”
Section: Cea Historical Perspectivementioning
confidence: 99%
“…The choice between prosthetic patch or vein patch appears to be less critical. 158,159 Observational studies For nonrandomized observational studies, the 30-day risk of perioperative stroke or death after CEA was approximately 7% for patients with symptomatic stenosis and 3% to 5% for patients with asymptomatic stenosis. 160,161 Stroke rates were higher in women, octogenarians, after repeat CEA, and in patients undergoing formal neurological evaluation.…”
Section: Techniquementioning
confidence: 99%